Propuesta de mejoras a la organización por procesos de la dirección de Talento Humano del Gobierno Autónomo Descentralizado Municipal de Tosagua - García Moreira, Bélgica Mercedes (2018)
The management of personnel in public institutions is very important for organizational development, so the investigation was carried out in the Municipal Autonomous Decentralized Government of Tosagua, proposing corrective actions to the organization by processes of the Human Talent Directorate, where it was found The Organic Law of the Public Service, through which an interview was applied that determines the role, the identification of human talent systems, in addition to the fact that a survey is applied to public servants where the main problems that the processes have complete in the entity, for what has been developed in an improvement plan, are the following: an institution to be able to provide standards of quality and efficiency a society.